Genetalia Personal Hygiene Education and Demonstration - Mawarti, Indah; Mulyani, Sri; Nurlinawati, Nurlinawati; Yusnilawati, Yusnilawati (Jurusan Keperawatan Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2023)
The problem related to personal genital hygiene is maintaining cleanliness. The aim of the service is to increase participants' knowledge in maintaining genetalia cleanliness in everyday life. Community service is carried out at the Jambi Province Mental Hospital. The number of participants was 40 people. The activity began with building a relationship of mutual trust and entering into a time contract. The activity began with an opening, a pre-test, delivery of material using pictures and videos, a demonstration of cleaning women's genitalia, especially during menstruation using pantoms, evaluation of participants' responses, followed by a post-test. The results of the evaluation showed an increase in patient knowledge about personal genital hygiene. The results of participants' correct answers on the criteria of knowledge about the effects and risks of not maintaining personal hygiene and knowledge of the meaning of menstruation in the posttest were 100%, the pretest was 33 participants (82.5%), the correct answer was on the criteria of knowledge of personal hygiene methods during menstruation. in the pretest 27 participants (67.5%) and 38 participants (95%) in the posttest. Regarding the criteria for knowledge about alternative sanitary napkins, the results were 21 participants (52.5%) in the pre-test to 36 participants (90%) in the post-test. On the criteria of knowledge about how to maintain personal hygiene during menstruation, results were obtained from 20 participants (50%) in the pre-test to 36 participants (90%) in the post-test